2016
DOI: 10.1093/gbe/evw079
|View full text |Cite
|
Sign up to set email alerts
|

The Genome and Methylome of a Subsocial Small Carpenter Bee,Ceratina calcarata

Abstract: Understanding the evolution of animal societies, considered to be a major transition in evolution, is a key topic in evolutionary biology. Recently, new gateways for understanding social evolution have opened up due to advances in genomics, allowing for unprecedented opportunities in studying social behavior on a molecular level. In particular, highly eusocial insect species (caste-containing societies with nonreproductives that care for siblings) have taken center stage in studies of the molecular evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 100 publications
7
57
0
2
Order By: Relevance
“…4b and Supplementary Table 16). These results show strong parallels to findings for eusocial Hymenoptera [40][41][42][43] . This is in stark contrast to the non-eusocial cockroach, B. germanica, where there was only a very weak relationship between CpG o/e and differential expression between nymphs and adult females (r = 0.14), nor were any large differences apparent in enriched GO terms between putatively methylated and non-methylated genes (Fig.…”
Section: −16supporting
confidence: 86%
“…4b and Supplementary Table 16). These results show strong parallels to findings for eusocial Hymenoptera [40][41][42][43] . This is in stark contrast to the non-eusocial cockroach, B. germanica, where there was only a very weak relationship between CpG o/e and differential expression between nymphs and adult females (r = 0.14), nor were any large differences apparent in enriched GO terms between putatively methylated and non-methylated genes (Fig.…”
Section: −16supporting
confidence: 86%
“…260 We found patterns of CpG methylation to be in line with other insect species. It is mainly 261 focused in exons (Glastad et al, 2017), and high CpG methylation was associated with highly 262 expressed genes (Figure 3) (Arsenault et al, 2018;Bonasio et al, 2012;Glastad et al, 2013;Libbrecht et al, 2016;Patalano et al, 2015;Wang et al, 2013), and non-differentially expressed 264 genes showed higher levels of methylation (Glastad et al, 2013(Glastad et al, , 2016Libbrecht et al, 2016;Sarda 265 et al, 2012). Neonicotinoids appear to have no effect on overall levels of CpG methylation (see wasp's (Nasonia) genome lacked non-CpG DNA methylation , and in this study, while we identified 270 a very small number of loci showing methylation in CHG/CHH contexts, we could not exclude the 271 possibility that much of it was noise, as bisulfite sequencing is prone to false positives from sources 272 such as incomplete bisulfite conversion, miscalled bases and SNPs.…”
mentioning
confidence: 99%
“…We therefore mined the Sodalis data from several previously collected genomic sequencing datasets, including 150 samples of the socially polymorphic Lasioglossum albipes and individual samples of 12 other halictid species. We also included all shotgun sequencing data collected for the five bee genomes sequenced in Kapheim et al (49) and Ceratina calcarata (50). We recovered large amounts of Sodalis data from 36 of the 150 L. albipes samples as well as six other halictids (H. ligatus, L. calceatum, L. leucozonium, L. malachurum, L. marginatum, and L. vierecki) and C. calcarata (Fig.…”
Section: Sodalis Phylogenymentioning
confidence: 99%
“…In addition, we made use of previously collected sequencing data for 13 other halictid species: Augochlorella aurata, Augochlora pura, Agapostemon virescens, Lasioglossum leucozonium, L. figueresi, L. marginatum, L. vierecki, L. zephyrum, L. calceatum, L. malachurum, L. oenotherae, L. pauxillum, and Halictus ligatus. Finally, to determine how widespread Sodalis is across bees, we also downloaded all raw data (excluding mate-pair libraries) sequenced as part of the 10 bee genome project (49) and for the Ceratina calcarata genome sequencing project (50). All raw datasets were filtered using the same methodology as the L. albipes dataset.…”
Section: Evolutionary History Of Halictid-associated Sodalismentioning
confidence: 99%